Effects of Cytokinin and Auxin on In Vitro Organ Development and Plumbagin Content of Drosera peltata Thunb. - Thanakorn Wongsa; Phithak Inthima; Maliwan Nakkuntod; Duangporn Premjet; Anupan Kongbangkerd (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
A rapid propagation and plumbagin production of Drosera peltata was developed and investigated. The research aims to study the effects of cytokinins and auxins on organ development and plumbagin production from shoot tip cultures. In vitro generated shoot tips were cultured on the semi-solid 1/2 MS medium containing 3.0% sucrose, 2.0% gelrite, and 0.1, 0.5, 1.0, and 2.0 mg L–1cytokinins (BA, Kn, TDZ) and auxins (IAA, IBA, NAA and 2,4-D) for 12 weeks. The highest number of shoots (12.0 ± 1.2) was formed on the medium containing 1.0 mg L–1 TDZ, which was four-fold higher than in the control. Meanwhile, the highest number of roots per explant (9.4 ± 1.3) and rhizomes per explant (8.1 ± 0.8) were formed on the medium containing 2.0 mg L–1 NAA. The best callus induction (100%) was found on the 0.5–2.0 mg L–1 2,4-D-containing medium. Moreover, the highest plumbagin content (12.04 mg g–1 DW) was detected from shoots regenerated on the 0.1 mg L–1 BA-containing medium, which was approximately two-fold higher than that in the control. The study is efficient for organs induction and enhances plumbagin content from shoot tip explants of D. peltata.